2023
DOI: 10.1590/1807-3107bor-2023.vol37.0123
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic dental injuries in children: experience during the Covid-19 pandemic and parents’ knowledge about their management

Fernanda Jobim Mattos PAIXÃO,
Matheus da Silva Netto NASCIMENTO,
Nara Muniz LOPES
et al.

Abstract: The social isolation measures adopted during the critical phase of the COVID-19 pandemic led children to spend most of their time at home. Isolation may alter the pattern of traumatic dental injury occurrences, inasmuch as studies point out that most traumatic accidents occur at home. Considering this scenario and the influence of emergency management on the prognosis of the injury, the aim of this study was to evaluate the experience of traumatic dental injuries in children before and during the pandemic, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The importance of immediate attention for the handling of TDIs has been emphasised [13,15]. We observed that a considerable proportion of our study population reported previous TDIs.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The importance of immediate attention for the handling of TDIs has been emphasised [13,15]. We observed that a considerable proportion of our study population reported previous TDIs.…”
Section: Discussionmentioning
confidence: 79%
“…From this perspective, the availability and quality of emergency services at after-hours clinics are very important as optimal emergency management might be crucial for the TDI prognosis. The importance of immediate attention for the handling of TDIs, is gradually being recognised by the guardians of children [15].…”
Section: Introductionmentioning
confidence: 99%